2011
DOI: 10.1021/ja111389r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of the Ru-Catalyzed Hydroamidation of Terminal Alkynes

Abstract: The ruthenium-catalyzed hydroamidation of terminal alkynes has evolved to become a broadly applicable tool for the synthesis of enamides and enimides. Depending on the catalyst system employed, the reaction leads chemo-, regio-, and stereoselectively to a single diastereoisomer. Herein, we present a comprehensive mechanistic study of the ruthenium-catalyzed hydroamidation of terminal alkynes, which includes deuterium-labeling, in situ IR, in situ NMR, and in situ ESI-MS experiments complemented by computationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 119 publications
1
48
0
Order By: Relevance
“…addition to C−C triple bonds . Recently, a comprehensive description of the various mechanistic approaches for Ru‐catalyzed nucleophilic addition reactions of terminal alkynes was nicely compiled by Gooßen et al . They considered several potential mechanisms to evaluate the scope of the catalyst towards reactivity and selectivity in hydroamidation reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…addition to C−C triple bonds . Recently, a comprehensive description of the various mechanistic approaches for Ru‐catalyzed nucleophilic addition reactions of terminal alkynes was nicely compiled by Gooßen et al . They considered several potential mechanisms to evaluate the scope of the catalyst towards reactivity and selectivity in hydroamidation reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Caulton and co‐workers demonstrated a separate route for the vinylidene formation involving a neutral vinyl intermediate, referred to as route R 4 in Scheme . DFT calculations revealed that the Ru II ‐vinyl intermediate formed after insertion of π‐coordinated alkynes into the Ru−H bond can easily rearrange to a neutral vinylidene complex as in case of hydroamidation and other addition reactions . Unfortunately, a similar route is not operational for 9 III owing to the absence of a Ru−H bond, which is essential for vinyl intermediate formation.…”
Section: Resultsmentioning
confidence: 99%
“…For a few systems, the ReactIR setup has made the determination of accurate kinetic parameters possible, [31,32] but the technique is typically only used as a qualitative, complimentary tool to monitor the progress of a reaction and observe intermediates. [33][34][35][36] Here, it is shown that it can indeed be an even more powerful tool that has allowed the direct observation of a catalytically inactive oxorhenium diolate during the reaction. Furthermore, the monitoring of the consumption of reactants and formation of products has rendered the discovery of an unexpected acceleration towards the end of the DODH possible.…”
Section: Introductionmentioning
confidence: 98%
“…Under catalytic conditions, such acids react with the amine substrate present in situ to generate ammonium salts, which can be an adventitious proton source to push the catalytic reaction forward while simultaneously reducing the propensity for the amines to act as preferred ligands for metal coordination. Indeed, hydroamination frequently cannot be realized by using late transition metal complexes; however, hydroamidation and hydrocarbamation can be carried out efficiently due to the reduced nucleophilicity of these amine substrates [122][123][124][125][126][127]. Many recent advances take advantage of this class of protected amine reagents and will be briefly addressed here; however, this chapter focuses on hydroamination using the more challenging unprotected amine substrates.…”
Section: Introductionmentioning
confidence: 99%